Quantitative Relationships Between Structure and Activity of Gamma-Carboline Derivative Compounds as Anti-Bovine Viral Diarrhea Virus (BVDV) Using Semi-Empirical AM1 Method - Mutista Hafshah; Irvan Maulana Firdaus; Suratno Suratno (Walisongo Journal of Chemistry, 2022)
This research aims to study the quantitative structure and activity relationship (QSAR) of gamma-carboline derivative compounds as anti-BVDV agents to get an equation that can predict the value of the anti-BVDV activity of gamma-carboline derived compounds. The research material is experimental EC50 data that convert to anti-BVDB activity. 14 gamma-carboline derivative compounds are divided into 2 groups, namely, 11 fitting compounds and 3 test compounds. QSAR analysis is based on multilinear regression calculations of the fitting compound by plotting the EC50 log as the dependent variable and the descriptor as the independent variable. The used descriptors are atomic net charge (q) and dipole moment (µ), which are involved in calculations using the AM1 semiempirical quantum mechanics method. In addition, the partition coefficient of n-octanol/water (Log P), molecular polarizability (α), molecular weight (BM), Van Der Waals surface area (A vdw), Van Der Waals volume (V vdw), and index of refraction (RD) are obtained from QSAR properties. The resulting QSAR equation is: Log pEC50 = -48.670 – 124.801 (qC11) – 12.661 (α) – 0.918 (µ) – 0.876 (RD) – 0.999 (Log P) + 1.863 (BM) + 0.043 (V vdw) with n = 14; r = 0.937; r2 = 0.878; SD = 0.244; Fcount/Ftable = 1.466; PRESS = 0.749; Sig. = 0.02 This equation can be used as an initial guide for designing the structure of new compounds of the gamma-carboline class by considering some of the most influential descriptors. Consequentially, new compounds can be designed that have a smaller predicted EC50 value than the known compounds derived from gamma-carboline.